From fatwa to social media: Unleashing global muslim solidarity through fatwa and digital activism movement - Muhammad Fahmi Reksa Alfarisi; Ahmad Nashikhul Huda; Almeyda Asharsyira (Islamic Communication Journal, 2024)
The Israel-Palestine war has brought an enormous amount of attention to religious tension, global solidarity, and humanitarian movement in the Muslim world. This study investigates the underlying factor behind the fatwa issuance and its impact on the new trend of global solidarity in the digital sphere. The theory of mediation of meaning and new media by Hoover has been used to navigate the Fatwa of the Indonesian Ulama Council. This fatwa, regarding boycotts, divestments, sanctions movement, and the spread of Julid Fisabilillah digital activism, is a significant factor in shaping global Muslim solidarity. The digital activism is conducted by Indonesian and Malaysian netizens on specific social media platforms such as X, Instagram, and Telegram. This paper aims to contribute to the promotion of solidarity, compassion, and moral principles as fundamental aspects of humaneness. The research methods involved using a desk research methodology to collect data by analyzing scientific papers, digital media such as news, social media platforms, and literature reviews. The results indicated that this new trend of movements served as a means of expressing concern and advocating for humanity's values. It also aimed to create social justice and beneficial impact through humanitarian aid and establish emotional and moral connections to the Palestinian cause. Subsequently, the elements of religious tension, intrinsic and extrinsic religiosity, have intertwined roles in influencing this situation.*****Perang antara Israel-Palestina telah menyita banyak perhatian dari mulai esensi ketegangan agama, solidaritas global, hingga gerakan kemanusiaan di dunia Muslim. Studi ini berusaha untuk menyelidiki faktor yang mendasari diterbitkannya Fatwa Majelis Ulama Indonesia (MUI) terkait dukungan terhadap Palestina dan dampaknya terhadap tren baru solidaritas global di ranah digital. Teori mediasi makna dan media baru oleh Hoover diaplikasikan untuk menavigasi dampak dari Fatwa Majelis Ulama Indonesia yang berkenaan dengan gerakan boikot, divestasi, sanksi terhadap produk yang mendukung Israel dan penyebarannya melalui aktivisme digital Julid Fisabilillah yang banyak digalakkan oleh warganet Indonesia dan Malaysia di beberapa platform media sosial seperti X, Instagram dan Telegram. Tulisan ini memiliki kontribusi untuk meningkatkan solidaritas, kasih sayang, dan menegakkan prinsip-prinsip moral sebagai aspek dasar kemanusiaan. Metode penelitian yang digunakan adalah metode kepustakaan untuk mengumpulkan data dengan menganalisis beberapa karya ilmiah terdahulu, media digital seperti berita, platform media sosial, dan tinjauan literatur. Hasil penelitian menunjukkan bahwa tren gerakan baru ini berfungsi sebagai sarana efektif untuk mengekspresikan kepedulian dan mengadvokasi nilai-nilai kemanusiaan yang bertujuan untuk menciptakan keadilan sosial dan dampak yang bermanfaat melalui bantuan kemanusiaan, membangun hubungan emosional dan moral sejalan dengan perjuangan warga Palestina. Selanjutnya, elemen-elemen ketegangan agama, baik religiusitas intrinsik maupun ekstrinsik, memiliki peran yang saling terkait dalam mempengaruhi situasi ini.